2018
DOI: 10.1007/s13205-018-1377-x
|View full text |Cite
|
Sign up to set email alerts
|

Inulin chain length modification using a transgenic approach opening new perspectives for chicory

Abstract: Chicory capable of synthesizing long-chain inulin is of great interest. During the growing season, the sucrose-sucrose 1-fructosyltransferase (1-SST) activity is vital for production of long-chain inulin in chicory. With the purpose to increase inulin chain length, we employed -mediated transformation method. Transgenic chicory plants ( L. var. ) cv. 'Melci' has been developed to overexpress sucrose-sucrose 1-fructosyltransferase (1-SST) under the control of the CaMV 35S promoter. The integration of the T-DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The analyses of the transgenic lines proved that the CaMV35S promoter is suitable for overexpression strategies also in cardoon cells, as already shown for other Asteraceae such as artichoke [ 62 ], chicory ( Cichorium intybus var. sativum L., [ 63 ]), and gerbera ( Gerbera jamesonii , [ 64 ]). The three independent lines selected for this study overexpressed the transgene at significantly different levels, allowing for the exploration dose-dependent phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses of the transgenic lines proved that the CaMV35S promoter is suitable for overexpression strategies also in cardoon cells, as already shown for other Asteraceae such as artichoke [ 62 ], chicory ( Cichorium intybus var. sativum L., [ 63 ]), and gerbera ( Gerbera jamesonii , [ 64 ]). The three independent lines selected for this study overexpressed the transgene at significantly different levels, allowing for the exploration dose-dependent phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The artichoke 1-SST gene (GenBank: Y09662.1) forward primer 5'-CGAGATAGGCACAGCAACAC-3' reverse primer 5'-GCTTCAAGCGTCGATTCCAA-3' and artichoke 1-FFT gene (GenBank: AJ000481.2) forward primer 5'-GGAAGGTTCTTTGCGTCGAA-3' reverse primer 5'-CGTCTTGGTCGTAACTGTCG-3', were used. The artichoke ACTIN gene (GenBank: AM744951.1) forward primer 5'-TGCTGGATTCTGGAGATGGT-3' reverse primer 5'-ATCAAGACGGAGGATGGCAT-3', was used as an endogenous reference to normalize, as reported by Marou et al (2018). The results were analyzed using STEP One Software 2.0 (Applied Biosystems), using the 2 −ΔΔCt method (Schmittgen and Livak 2008).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…Specifically, 1-SST is responsible for transferring the fructosyl moiety from one sucrose molecule to another to form a 1-kestose and release a glucose molecule, via the irreversible reaction: ( Edelman and Jefford, 1968 ; Koops and Jonker, 1994 ; Lüscher et al, 1996 ; Van Den Ende et al, 1996 ). A recent study showed that overexpression of 1-SST was essential for production of long-chain inulin in chicory ( Maroufi et al, 2018 ). In addition, fructans, like starch and sucrose, are important stored forms of carbohydrate, and are also closely related to the regulation of plant carbon allocation and sucrose-pool ( Pollock, 1986 ; Nelson and Spollen, 1987 ).…”
Section: Introductionmentioning
confidence: 99%